Development of colonic neoplasia in p53 deficient mice with experimental colitis induced by dextran sulphate sodium. Issue 5 (13th April 2004) - Fujii, S; Fujimori, T; Kawamata, H; Takeda, J; Kitajima, K; Omotehara, F; Kaihara, T; Kusaka, T; Ichikawa, K; Ohkura, Y; Ono, Y; Imura, J; et al.
Abstract : Background: Several animal models for human ulcerative colitis (UC) associated neoplasia have been reported. However, most neoplasias developed in these models have morphological and genetic characteristics different from UC associated neoplasia. Aims: To establish a new colitis associated neoplasia model in p53 deficient mice by treatment with dextran sulphate sodium (DSS). Methods: DSS colitis was induced in homozygous p53 deficient mice (p53 −/− -DSS), heterozygous p53 deficient mice (p53 +/− -DSS) and wild-type mice (p53 +/+ -DSS) by treatment with 4% DSS. Numbers of developed neoplasias were compared among the experimental groups, and macroscopic and microscopic features of the neoplasias were analysed. Furthermore, K-ras mutation and beta-catenin expression were assessed. Results: p53 −/− -DSS mice showed 100% incidence of neoplasias whereas the incidences in p53 +/− -DSS and p53 +/+ -DSS mice were 46.2% and 13.3%, respectively. No neoplasias were observed in the control groups. The mean numbers of total neoplasias per mouse were 5.0 (p53 −/− -DSS), 0.62 (p53 +/− -DSS), and 0.2 (p53 +/+ -DSS). The number of neoplasias per mouse in the p53 −/− -DSS group was significantly higher than that in the other DSS groups. The incidences of superficial type neoplasias were 91.7% in p53 −/− -DSS mice, 75.0% in p53 +/− -DSS mice, and 33.3% in p53 +/+ -DSS mice. The K-ras mutation was not detected in any of the neoplasias tested. Translocation of beta-catenin from the cell membrane to the cytoplasm or nucleus was observed in 19 of 23 (82.6%) neoplasias. Conclusions: The p53 −/− -DSS mice is an excellent animal model of UC associated neoplasia because the morphological features and molecular genetics are similar to those of UC associated neoplasia. Therefore, this model will contribute to the analysis of tumorigenesis related to human UC associated neoplasia and the development of chemopreventive agents.